Eco-Romanticism Revisited: Nature as Political Witness in Byron, Keats, and Shelley: https://doi.org/10.55966/assaj.2025.4.1.066 - Ch Muhammad Uzair Chohan; Sidra Jamil (`, 2025)
This paper looks back over Romantic poetry of Byron, Keats, and Shelley through the perspective of eco-Romanticism and offers an alternative view of nature; not as a source of beauty or spiritual contemplation but as an alert votary. Instead of presenting it as an inert background, nature in their works is made active in the form of winds, mountains, rivers as well as the seasons as silent and mute witnesses of historical trauma, imperial rot, revolutionary spirit, and social change. Investigating a group of poems, including Childe Harold Pilgrimage by Byron, Ode to the West Wind by Shelley, and To Autumn by Keats, the research argues that nature in the poems of these three authors is a symbolic record of the human violence, struggle, and loss. Such a reading allows ecocriticism to meet political historicism, discovering sub today ignored environmental sensibility in their poetic imaginations. By so doing, the paper goes on to provide a more politicized interpretation of Romantic nature, which exposes how the three most significant uses of the natural world by the poets are not only enlisted in the criticism of empire, modernity, and the breaking apart of enlightenment ideals. Keywords: Eco-Romanticism,Nature and Politics, Romantic Poets, Byron, Keats, Shelley, Literature and Environment